Rekalkulasi Transformasi Kelompok Penekan Menjadi Partai Politik: Kajian pada Hizbut Tahrir Indonesia - M. Zainuddin; Suryaningsih (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2017)
The article to analyzes the opportunities Hizbut Tahrir Indonesia for transform of pressure group into a political party. This study stems from the analysis of a pressure group or organization that has been in Indonesia and ever tried to transform itself into a political party. This study took more cases in Pekanbaru. The results of the analysis of the strengths and opportunities describe Hizbut Tahrir Indonesia and predicting his desire to become a political party contestants elections in Indonesia in the future. The results of this study found a new theory about the transformation of a pressure group into a political party. Hizbut Tahrir Indonesia has conducted political movements from the beginning until now. Ideals end of Hizbut Tahrir Indonesia is to establish the Khilafah Islamiyah. In the concept of a single -party system, then the Khilafah Islamiyah may be referred to as having a single-party system in the party system of a country.